IMPLEMENTASI PENDIDIKAN KARAKTER DI SEKOLAH - Zulhijrah Zulhijrah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2015)
Character education in Indonesia felt sorely need to develop when considering the increasingly growing Brawl between students, as well as other forms of juvenile delinquency more especially in the big cities, blackmail/violence (bullying), drug use, and others. Therefore, the concept of character education must take a clear position, that person's characteristics can be shaped through education. Such education is capable of forming such characteristics, the answer to the question is what is known as character education.